The Origins of Anti-Authoritarianism - Witoszek, Nina (Critical Interventions, 2019)
This book discusses the ongoing revolution of dignity in human history as the work of 'humanist outliers': small groups and individuals dedicated to compassionate social emancipation. It argues that anti-authoritarian revolutions like 1989's 'Autumn of the Nations' succeeded in large part due to cultural and political innovations springing from such small groups. The author explores the often ingenious ways in which these maladapted and liminal 'outliers' forged a cooperative and dialogic mindset among previously resentful and divided communities. Their strategies warrant closer scrutiny in the context of the ongoing 21st century revolution of dignity and efforts to (re)unite an ever more troubled and divided world.